Experimental investigation on semicircular, triangular and rectangular shaped absorber of solar still with nano-based PCM - Goshayeshi, Hamid Reza; Chaer, Issa; Yebiyo, Metkel; Öztop, Hakan Fehmi (Springer, 2022)
This paper shows the results of a novel research conducted with the overall aim of developing a system that can provide continuous desalination. Productivity enhancement of solar stills is regarded as the main purpose of the investigators in desalination field. This paper represents the experimental results in a new approach of paraffin + graphene oxide nanoparticles mixture. The paraffin mixture in a semicircular, triangular and rectangular absorber with paraffin + graphene oxide of 0.1, 0.3 and 0.5 mass% has been investigated. The finding indicated that for all absorbers, the use of paraffin + graphene oxide in higher mass fractions enhances daily freshwater production. The results showed that the thermal performances are greater applying graphene oxide + paraffin of 0.5 mass% with semicircular absorber compared to triangular and rectangular absorber. The achievement of the present paper can be implemented to design more efficient absorbers for solar still parts.
Keywords: Solar still; Paraffin with graphene oxide; Different shapes; Rectangular; Triangular; Semicircular; Absorbers